Developing and piloting a peer quality improvement coaching protocol for front-line healthcare staff - Siobhán Eithne McCarthy; Petar Popivanov; Mairead Finn (BMJ Open Quality)
Background Improving the quality of patient care remains a global necessity. Despite system and professional benefits, current evidence indicates that the spread of improvement principles among front-line healthcare workers remains poor.While education and training alone are unlikely to result in consistent improvement practice, coaching can play a critical role in sustainable, evidence-based improvement implementation. Peer quality improvement coaching (PQIC) places the power and agency in the shared relationship between coach and coachee to shape coachee quality improvement (QI) outcomes.Study objective was to develop and pilot an evidence-based protocol for implementation and evaluation of a PQIC for front-line staff engaged in small to intermediate improvement efforts.Methods We conducted a multistage case-study design and implementation process. First, a systematised literature review identified themes about the theory and practice of QI coaching (QIC). Second, these themes guided the development of a PQIC protocol. Finally, the protocol was piloted and evaluated among staff in a single-centre tertiary maternity hospital. PQIC effectiveness was assessed using evaluation tools identified in the literature.Results Effectiveness; strategies and models; moderating factors and methods for evaluation of QIC emerged from the literature. Together with Bloom’s taxonomy and Kirkpatrick’s educational model, these themes informed the development of this PQIC protocol. It was piloted in three steps: education, coaching and evaluation. A survey revealed that the participants in the education step achieved excellent scores. Following the coaching journey, the coached multidisciplinary team leaders completed their improvement initiatives and demonstrated increased QI knowledge and skills measured by the ‘IHI improvement advisor self-assessment tool’ and ‘IHI assessment scale for collaboratives’.Conclusion Built on established education, peer coaching and QI concepts, this evidence-based PQIC protocol adds to international evidence on how to support front-line healthcare workers in their improvement efforts. Future research needs to assess protocol effectiveness across different settings.